HIV/HCV coinfection ameliorates the atherogenic lipoprotein abnormalities of HIV infection - WHEELER, Amber L. (AIDS, 2014)
BACKGROUND: Higher levels of small low-density lipoprotein (LDL) and lower levels of high-density lipoprotein (HDL) subclasses have been associated with increased risk of cardiovascular disease. The extent to which HIV infection and HIV/HCV coinfection are associated with abnormalities of lipoprotein subclasses is unknown. METHODS: Lipoprotein subclasses were measured by nuclear magnetic resonance (NMR) spectroscopy in plasma samples from 569 HIV-infected and 5948 control participants in the FRAM, CARDIA and MESA studies. Multivariable regression was used to estimate the association of HIV and HIV/HCV coinfection with lipoprotein measures with adjustment for demographics, lifestyle factors, and waist-to-hip ratio. RESULTS: Relative to controls, small LDL levels were higher in HIV-monoinfected persons (+381 nmol/L, p<.0001), with no increase seen in HIV/HCV coinfection (−16.6 nmol/L). Levels of large LDL levels were lower (−196 nmol/L, p<.0001) and small HDL were higher (+8.2 μmol/L, p<.0001) in HIV-monoinfection with intermediate values seen in HIV/HCV-coinfection. Large HDL levels were higher in HIV/HCV-coinfected persons relative to controls (+1.70 μmol/L, p<.0001), whereas little difference was seen in HIV-monoinfected persons (+0.33, p=0.075). Within HIV-infected participants, HCV was associated independently with lower levels of small LDL (−329 nmol/L, p<.0001) and small HDL (−4.6 μmol/L, p<.0001), even after adjusting for demographic and traditional cardiovascular risk factors. CONCLUSION: HIV-monoinfected participants had worse levels of atherogenic LDL lipoprotein subclasses compared with controls. HIV/HCV coinfection attenuates these changes, perhaps by altering hepatic factors affecting lipoprotein production and/or metabolism. The effect of HIV/HCV coinfection on atherosclerosis and the clinical consequences of low small subclasses remain to be determined.